Upaya Peningkatan Hasil Belajar dan Motivasi Belajar Mahasiswa PGSD Universitas Jember Melalui Penerapan Pembelajaran Problem-Based Learning pada Mata Kuliah Konsep Dasar IPS: Efforts to Improve Learning Outcomes and Learning Motivation of PGSD Students at the University of Jember Through the Application of Problem-Based Learning in Social Science Basic Concepts Courses - Rahayu, Rahayu (Pedagogia : Jurnal Pendidikan, 2018)
This study aims to find out the application of learning problem base learning to improve social studies learning outcomes and student learning motivation in the Social Sciences Basic Concepts of Jember University. The research method uses a qualitative research paradigm with a classroom action research approach with the Kemmis and Mc Taggart spiral model with the flow of planning, action, observation and reflection carried out in cycle I and cycle II. Data collection techniques in research through interviews, observation, giving questionnaires, and tests. The results of the implementation of problem based learning learning activities in the first cycle were carried out with a percentage of 85%, and in the second cycle it was carried out with a percentage of 90%. Cognitive learning outcomes of students in the first cycle reached 80% with very good average scores above the KKM (minimum completeness criteria) set, and in cycle II with an average score reaching 100% with very good criteria. Learning motivation and cognitive learning outcomes of students in the basic concepts of social studies in the PGSD study program. Student learning motivation in the first cycle is very high and cycle II student learning motivation is very high after applying Problem based learning to the Basic Concepts of Social Sciences course.